Does prognosis and socioeconomic status impact on trust in physicians? Interviews with patients with coronary disease in South Australia. Issue 5 (3rd October 2012) - Meyer, Samantha B; Ward, Paul R; Jiwa, Moyez
Abstract : Objectives: There is concern across a range of healthcare settings worldwide that trust in physicians is declining. Decreased trust may lead to lesser tolerance of prognosis uncertainty and an increased demand for tests, referrals and second opinions. Literature suggests that there has been a recent cultural shift towards decreased trust in, and increased questioning of, medical advice. We investigated the impact of varying prognosis and socioeconomic status (SES) on trust in physicians, and patient questioning of medical advice. Design: Semistructured, audio-recorded transcribed interviews were conducted. The interview schedule was developed with reference to the Health Belief Model. Interviews were conducted between October 2008 and September 2009. Setting: Participants were recruited via general practitioner clinics and hospital cardiac rehabilitation programmes. Participants: Participants consisted of patients either receiving preventive treatment or active treatment for established cardiovascular disease. Outcome measures: A coding structure was developed based on the aim of the research, to investigate the impact of varying prognosis and SES on trust in physicians. Results: Older participants are more likely than their younger counterparts to be unquestioning of medical advice. Higher SES participants are more likely to question medical advice than lower SES participants. Also, unlike primary prevention participants, established pathology increased participants' trust, or decreased questioning behaviour. Participants who perceived themselves at risk of a poor or uncertain outcome were unlikely to doubt medical advice. Conclusions: Blind trust in physicians remains strong in older participants, participants who perceive their prognosis to be uncertain and a proportion of lower SES participants. This is important for practitioners in terms of patient agency and points to the importance of moral and ethical practice. However, physicians also need to be aware that there are a growing proportion of patients for whom trust needs to be developed, and cannot be assumed.